Improving E-Procurement in Supply Chain Through Web Technologies: The HYDRA Approach - Alor-Hernandez, Giner; Aguilar-Laserre, Alberto A.; Cortes-Robles, Guillermo; Sanchez-Ramirez, Cuauhtemoc (IntechOpen, 2011)
None